Leitbilder und strategische Raumentwicklung - Jörg Knieling (Raumforschung und Raumordnung, 2006)
Concepts should fulfil different functions in the framework of a strategic spatial development: orientation, co-ordination, reflection, innovation and activation. How can the new “Concepts and Policy Strategies for Spatial Development in Germany” be placed in this respect? The article considers the orientation of the concepts towards growth and the provision of essential services as well as the strategy “reinforcing strengths”, the concentration of metropolitan regions connected with this and the economic orientation of spatial development. Do objective conflicts result with the orientation towards balance and with the overriding concepts of a sustainable spatial development? Which perspectives are offered by the new instrument of “large-scale communities of responsibility”? And with regard to the planning method: How can concept processes guarantee the necessary openness and adaptability? Further-reaching research questions are derived from the discussion.